Analysis of High School Students' Learning Discipline in Physics Learning - Ria Ambarwati; Elwells B. Ulla; Mehdi Tajaddini (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: This research was conducted with the aim of finding out students' disciplinary attitudes towards physics subjects in high school. Methodology: This research uses a mixed methods explanatory design. The sampling technique uses simple random sampling. The number of samples in this study was 120 high school students. Data collection techniques used questionnaires and interviews. Data analysis uses descriptive statistics and miles and miles model. Data analysis in this research uses a quantitative approach using the SPSS program. Main Findings: It was found that student discipline was categorized as good and quite good. So, stimulus treatment from the teacher is needed to increase student learning discipline. The implication of this research is that it can help teachers and educational stakeholders to understand the factors that influence student learning discipline in Physics subjects. With better understanding, they can develop more effective learning strategies to increase student motivation and engagement. Novelty/Originality of this study: The novelty of the research may provide a better understanding of the dynamics of student learning in physics, enabling the development of more effective learning strategies